Changes in resting heart rate and blood pressure in response to resistance exercise training program - Angelheart Joy Maynard Rattu Angelheart Joy Maynard Rattu (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Previous studies showed that both systolic and diastolic blood pressures could be lowered to a modest degree with an aerobic type exercise.Objective: The present study was designed to explore the effect of resistance exercise training program on resting heart rate and blood pressure in males and females.Methods: Thirty-three normal healthy subjects participated in this study. Resting heart rate and resting blood pressure were measured before and after a weight-training program twice a week for eight weeks. Results: Data showed that resting heart rate was significantly (p) lower in males compared to that observed in females before and after the training program. A significant decrease in resting heart rate (p) was observed in both sexes as a result of the training program. Resting systolic and diastolic blood pressures were slightly (p = 0.08) lower in the female group compared to that observed in the male group before the training program. Resistance exercise training induced no significant change in resting systolic and diastolic blood pressures in both groups. After the training program, resting systolic and diastolic blood pressures were slightly (p=0.09) lower in the female group compared to that observed in the male group.Conclusion: Exercise stimulus in the form of circuit weight training was sufficient to elicit cardiovascular adaptations in response to training.Key words: resistance exercise training - heart rate - systolic and diastolic blood pressures -cardiovascular adaptations